Infrastructure development: compulsory purchase or land easement - Lizunova, Alina; Lytvynenko, Iryna (KNUCA, 2021)
Sustainable development requires the Governments of the countries to establish and maintain in a functional conditions social and engineering infrastructure facilities that provide security, healthy living conditions, well-being, socio-economic development, protection and restoration of the natural environment. To achieve the Sustainable Development Goals, the Ukraine 2020 Sustainable Development Strategy has been developed. The aim of the Strategy is to introduce European standards of living in Ukraine and Ukraine's leading position in the world.
Keywords: Infrastructure development; compulsory purchase; land easement; 332.36